The accuracy of hospital merger screening methods. (13th November 2017) - Garmon, Christopher
Abstract: This article analyzes the accuracy of various prospective hospital merger screening methods used by antitrust agencies and the courts. The predictions of the screening methods calculated with pre‐merger data are compared with the actual post‐merger price changes of 28 hospital mergers measured relative to controls. The evaluated screening methods include traditional structural measures (e.g., Herfindahl‐Hirschman Index), measures derived from hospital competition models (e.g., diversion ratios, willingness‐to‐pay, and upward pricing pressure), and hospital merger simulation. Willingness‐to‐pay and upward pricing pressure are found to be more accurate at flagging potentially anticompetitive mergers for further investigation than traditional methods.